Scented Visions : Smell in Art, 1850-1914 - Bradstreet, Christina (Book collections on Project MUSE., 2022)
Smell loomed large in cultural discourse in the late nineteenth century, thanks to the midcentury fear of miasma, the drive for sanitation reform, and the rise in artificial perfumery. Meanwhile, the science of olfaction remained largely mysterious, prompting an impulse to "see smell" and inspiring some artists to picture scent in order to better know and control it. This book recovers the substantive role of the olfactory in Pre-Raphaelite art and Aestheticism.Christina Bradstreet examines the iconography and symbolism of scent in nineteenth-century art and visual culture. Fragrant imagery in the work of John Everett Millais, Dante Gabriel Rossetti, Simeon Solomon, George Frederic Watts, Edward Burne-Jones, and others set the trend for the preoccupation with scent that informed swaths of British, European, and American art and design. Bradstreet's rich analyses of paintings, perfume posters, and other works of visual culture demonstrate how artworks mirrored the "period nose" and intersected with the most clamorous debates of the day, including evolution, civilization, race, urban morality, mental health, faith, and the "woman question."Beautifully illustrated and grounded in current practices in sensory history, Scented Visions presents both fresh readings of major works of art and a deeper understanding of the cultural history of nineteenth-century scent.